Probing the Kinetic Anabolism of Poly-Beta-Hydroxybutyrate in Cupriavidus necator H16 Using Single-Cell Raman Spectroscopy - Zhanhua, Tao; Lixin, Peng; Pengfei, Zhang; Yong-Qing, Li; Guiwen, Wang (My University, 2016)
Poly-beta-hydroxybutyrate (PHB) can be formed in large amounts in Cupriavidus necator and is important for the industrial production of biodegradable plastics. In this investigation, laser tweezers Raman spectroscopy (LTRS) was used to characterize dynamic changes in PHB content—as well as in the contents of other common biomolecule—in C. necator during batch growth at both the population and single-cell levels. PHB accumulation began in the early stages of bacterial growth, and the maximum PHB production rate occurred in the early and middle exponential phases. The active biosynthesis of DNA, RNA, and proteins occurred in the lag and early exponential phases, whereas the levels of these molecules decreased continuously during the remaining fermentation process until the minimum values were reached. The PHB content inside single cells was relatively homogenous in the middle stage of fermentation; during the late growth stage, the variation in PHB levels between cells increased. In addition, bacterial cells in various growth phases could be clearly discriminated when principle component analysis was performed on the spectral data. These results suggest that LTRS is a valuable single-cell analysis tool that can provide more comprehensive information about the physiological state of a growing microbial population.
Keywords: : Raman spectroscopy; laser tweezers; anabolism; poly-beta-hydroxybutyrate; single-cell analysis